Factores determinantes en la renovación del ERP de la empresa Novacero S.A. - Santacruz Rengifo, Eddy Geovanny (2021)
The objective of this project was to define the determining factors in the renewal of the ERP of the company NOVACERO S.A. For which, a bibliographic collection and case study was carried out, delimiting eleven critical factors for the implementation of ERP systems related to large organizations. Subsequently, the Kano methodology was implemented as a tool aimed at determining the needs of future users of the information system as internal customers, focused on the ERP system in product quality; For this, the tools implemented reflected the functional requirements for the areas of Finance, Sales, Production, Purchasing and Warehouses; and Human Resources, the same ones, which were classified into one-dimensional, mandatory, indifferent, doubtful and inverse factors. The work concludes by framing said content in the implementation proposal format, where the necessary phases for the proposal to be functional are expressed, to which, finally, the corresponding validation of the same carried out by experts and knowledgeable users of the subject is exposed. .